Analisis Penerimaan Pajak Hiburan Terhadap Peningkatan Pendapatan Asli Daerah (Studi Pada Pemerintah Daerah Kabupaten Gowa) - eldi (Insan Cita Bongaya Research Journal, 2022)
This study aims to determine the effect of entertainment tax revenue on Gowa Regency's Original Regional Revenue. Data collection uses secondary data obtained from the Regional Financial Management Office (DPKD) of Gowa Regency. The population is the recapitulation of Entertainment and Income Tax Receipts in DPKD Kab. Gowa from 2013 to 2015 which consisted of 36 months (n=36). The data has been tested for classical assumptions in the form of normality, autocorrelation, and heteroscedasticity. The analytical method used is a simple regression technique. The results showed that the proposed hypothesis was rejected, because it showed a positive but not significant hypothesis test result. This means that Entertainment Tax Revenue has a positive but not significant effect on Gowa Regency's Original Revenue.